Microtopographic and depth controls on active layer chemistry in Arctic polygonal ground. Issue 6 (24th March 2015) - Newman, B. D.; Throckmorton, H. M.; Graham, D. E.; Gu, B.; Hubbard, S. S.; Liang, L.; Wu, Y.; Heikoop, J. M.; Herndon, E. M.; Phelps, T. J.; Wilson, C. J.; Wullschleger, S. D.
Abstract Polygonal ground is a signature characteristic of Arctic lowlands, and carbon release from permafrost thaw can alter feedbacks to Arctic ecosystems and climate. This study describes the first comprehensive spatial examination of active layer biogeochemistry that extends across high‐ and low‐centered, ice wedge polygons, their features, and with depth. Water chemistry measurements of 54 analytes were made on surface and active layer pore waters collected near Barrow, Alaska, USA. Significant differences were observed between high‐ and low‐centered polygons suggesting that polygon types may be useful for landscape‐scale geochemical classification. However, differences were found for polygon features (centers and troughs) for analytes that were not significant for polygon type, suggesting that finer‐scale features affect biogeochemistry differently from polygon types. Depth variations were also significant, demonstrating important multidimensional aspects of polygonal ground biogeochemistry. These results have major implications for understanding how polygonal ground ecosystems function, and how they may respond to future change.